Dissociation kinetics of G proteins from G protein–coupled receptors and effects of allosteric modulation - Jinan Wang; Anh T. N. Nguyen; Victor A. Adediwura; Cam Sinh Lu; Samantha M. McNeill; Manuela Jörg; Peter J. Scammells; Arthur Christopoulos; Lauren T. May; Yinglong Miao (Proceedings of the National Academy of Sciences, 2025)
G protein–coupled receptors (GPCRs), the largest superfamily of human membrane proteins with >800 members, are primary targets for ~1/3 of all marketed drugs. Recent fluorescence experiments underscored the pivotal role of GPCR–G protein complex lifetime in their coupling efficiency and selectivity. However, these experiments are often expensive, time-consuming, and limited to a small number of GPCR–G protein systems. On the other hand, it is challenging to simulate GPCR–G protein dissociation using molecular dynamics (MD) methods. Here, we have employed Protein–Protein Interaction Gaussian accelerated MD (PPI-GaMD) simulations and experiments to probe the kinetics and pathways of G protein dissociation from GPCRs. For five systems with published experimental kinetic data, PPI-GaMD simulations successfully captured G protein dissociation from the GPCRs, including the adrenergic, adenosine, and muscarinic receptors. The simulations allowed identification of two distinct dissociation pathways and calculation of the G protein dissociation rates, which were in good agreement with experimental data. Additionally, we simulated the effect of positive allosteric modulators (PAMs) of the adenosine A 1 receptor (A 1 R) in Gi protein dissociation and supported simulation findings with bioluminescence resonance energy transfer biosensor experiments evaluating G βγ kinetics following A 1 R activation. A 1 R PAMs were found to strengthen the agonist–receptor and receptor–G protein interactions and significantly reduce dissociation rates of the Gi protein. In summary, complementary PPI-GaMD simulations and kinetic assays have enabled detailed characterization of the kinetics and pathways of G protein dissociation, a critical event in the GPCR signaling cascade, and the effects of GPCR allosteric modulators.